Sex Differences in Managerial Style : From Individual Leadership to Organisational Labour Relationships - Eduardo Melero (Institute for the Study of Labor (IZA), 2004)
This paper deals with sex differences in managerial behaviour, by testing the extent to which such differences match those expected from gender stereotypes. Unlike previous research on the topic, always based on opinions about individual managers, this investigation uses firm-level evidence from the British 1998 Workplace Employment Relationship Survey (WERS 98). This means that some problems usually present in individual-level studies, including answer stereotyping and selection of female managers into specific responsibilities, are avoided in the research presented here. The results show that workplaces where the presence of women at management is higher are driven in a more democratic fashion, with more interpersonal and interactive relationships between managers and subordinates, and with more employee-mentoring responsibilities undertaken by managers. No sex differences were found for more structural policies, such as the degree of delegation on supervisors or the extension of payment by results.
Keywords: J53; M54; 330; managerial style; gender behavioural differences; human resources policies; Führungskräfte; Geschlecht; Weibliche Führungskräfte; Führungstheorie; Grossbritannien